answersLogoWhite

0


Best Answer

If you mean: 2x-5y+2z = 16 and 3x+2y-3z = -19 and 4x-3y+4z = 18 then the solutions are found as follows:-

3(2x-5y+2z = 16) => 6x-15y+6z = 48

2(3x+2y-3z = -19) => 6x+4y-6z = -38

Adding the above: 12x-11y = 10 thus eliminating z

4(3x+2y-3z = -19) => 12x+8y-12z = -76

3(4x-3y+4z = 18) => 12x-9y+12z = 54

Adding the above: 24x-y = -22 thus eliminating z

2(12x-11y = 10) => 24x-22y = 20

1(24x-y = -22) => 24x-y = -22

Subtracting the above: -21y = 42 thus eliminating x

If: -21y = 42 then y = -2

So by substitution: x = -1, y = -2 and z = 4

Check: (2*-1)-(5*-2)+(2*4) = 16

Check: (3*-1)+(2*-2)-(3*4) = -19

Check: (4*-1)-(3*-2)+(4*4) = 18

User Avatar

Wiki User

โˆ™ 2013-10-17 11:45:20
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.79
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1456 Reviews

Add your answer:

Earn +20 pts
Q: How do you solve these equations by substitution 2x-5y plus 2z equals 16 3x plus 2y-3z equals -19 4x-3y plus 4z equals 18?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Continue Learning about Other Math
People also asked